2022
DOI: 10.1038/s41598-022-12475-z
|View full text |Cite
|
Sign up to set email alerts
|

Children with autism spectrum disorder show atypical electroencephalographic response to processing contextual incongruencies

Abstract: Children with autism spectrum disorder (ASD) experience difficulties with social communication, making it challenging to interpret contextual information that aids in accurately interpreting language. To investigate how the brain processes the contextual information and how this is different in ASD, we compared event-related potentials (ERPs) in response to processing visual and auditory congruent and incongruent information. Two groups of children participated in the study: 37 typically developing children an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 95 publications
(89 reference statements)
0
11
0
Order By: Relevance
“…Fourth, larger trial numbers are optimal for connectivity estimates to attenuate variability and possible biases in increased connectivity; however, data acquisition is challenging in developmental populations, especially in those with neurodevelopmental disorders, limiting the number of non-target trials post-artifact rejection that were included in the present analyses ( Pang, 2011 , Taylor and Pang, 2014 , Puce and Hämäläinen, 2017 ). We chose a 20 non-target trial per emotion threshold, consistent with previous MEG/EEG studies ( Márquez-García et al, 2022 , Fogelson et al, 2019 , Naumann et al, 2018 ), to maximize the number of participants included in the analyses and to avoid biasing our population towards those who are older and higher-functioning. Lastly, MEG data from all participants were recorded in the supine position, which minimizes head movement and stabilizes the head in the MEG dewar facilitating data collection in developmental populations.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, larger trial numbers are optimal for connectivity estimates to attenuate variability and possible biases in increased connectivity; however, data acquisition is challenging in developmental populations, especially in those with neurodevelopmental disorders, limiting the number of non-target trials post-artifact rejection that were included in the present analyses ( Pang, 2011 , Taylor and Pang, 2014 , Puce and Hämäläinen, 2017 ). We chose a 20 non-target trial per emotion threshold, consistent with previous MEG/EEG studies ( Márquez-García et al, 2022 , Fogelson et al, 2019 , Naumann et al, 2018 ), to maximize the number of participants included in the analyses and to avoid biasing our population towards those who are older and higher-functioning. Lastly, MEG data from all participants were recorded in the supine position, which minimizes head movement and stabilizes the head in the MEG dewar facilitating data collection in developmental populations.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 14 articles and 18 studies were included for applying the linguistic stimuli [30][31][32][33][34][35][36][37][38][39][40][41][42][43] . Five effect sizes were computed to examine the N400 and P600 responses under the linguistic stimulus, including N400 amplitude, N400 different wave, N400 amplitude for congruent condition, N400 amplitude for incongruent condition, and P600 amplitude.…”
Section: Erp Component Elicited By Linguistic Stimulusmentioning
confidence: 99%
“…The heterogeneity was moderate for the P600 amplitude difference to speech sound stimulation and the xed effect model was applied for analysis (Q = 12.516, I 2 = 44.073). Among the 8 studies, only 2 studies revealed a late positive potential 37,40 and most studies reported a sustained negativity. The effect size was signi cant, indicating greater negativity in the control group compared to the ASD group (Hedges' g = 0.289, 95% CI ranged from 0.059 to 0.518, P = 0.014, Fig.…”
Section: P600 Amplitude Difference Between Asd and Controlsmentioning
confidence: 99%
“…In 14 articles and 18 studies, the N400 and P600 were elicited by linguistic stimuli [18,21,22,[32][33][34][35][36][37][38][39][40][41][42]. Among the linguistic stimuli, some were presented with sentence in the semantic anomalies paradigm; the others were presented with words in the semantic priming paradigm or in-category and outof-category words paradigm.…”
Section: Erp Component Elicited By Linguistic Stimulusmentioning
confidence: 99%
“…Five effect sizes were computed to examine the N400 and P600 responses under the linguistic stimulus, including N400 amplitude, N400 different wave, N400 amplitude in congruent condition, N400 amplitude in incongruent condition, and P600 amplitude. The N400 amplitudes difference under linguistic stimulus Thirteen articles and 17 studies compared N400 amplitude differences elicited by linguistic stimuli between autistic and nonautistic group [18,21,22,[32][33][34][35][36][37][38][39][40][41]. The sample size of the two groups were 218 and 237, respectively.…”
Section: Erp Component Elicited By Linguistic Stimulusmentioning
confidence: 99%